The Development of Local Wisdom-Based Chemistry Modules to Improve Students' Science Process Skills - Dominggus Tahya; Franklin Stevan Dahoklory; Sendry Richard Dahoklory (Postgraduate, University of Mataram, 2022)
Process skills are essential skills that must be possessed in the chemistry learning process. It is because science process skills are needed in conducting scientific investigations. This study aimed to develop a chemistry subject module based on local wisdom and its effectiveness in improving students' science process skills. The research subjects were 30 eleventh grade senior high school students. This development research used the Borg and Gall model (2003), which adapts the Dick and Carey model, named Instructional System Design which includes ten stages of development. The product of this research and development is a chemistry subject module for the subject of colloid systems. Furthermore, the developed module received a validation test using a questionnaire given to experts and users to determine its feasibility in learning. The results of feasibility validation by learning media experts obtained a percentage of 100%, by chemists on the chemical material presented in the module content of 91%, by chemistry learning experts with a percentage of 82.50%, by 10 students with a percentage of 91.43%. Thus, the module developed is very feasible to be used in learning. After getting validation, the science process skills test results were analyzed on the initial and final tests using the Normalized Gain (N-gain) technique to determine its effectiveness in improving students' science process skills. Data analysis was obtained through one group pre-test and post-test design. Then, the results of the N-gain analysis of 0.74 are categorized as